Moderne Modifikationen der Uvulopalatopharyngoplastik = Modern modifications of uvulopalatopharyngoplasty - Verse, Thomas; Stuck, Boris (HNO, 2017)
Uvulopalatopharyngoplasty (UPPP) was first described in 1964 with regard to surgical treatment of snoring and in 1981 with regard to treatment of obstructive sleep apnea (OSA). The initial surgical techniques for OSA were very invasive, frequently leading to significant morbidity and complications. Wolfgang Pirsig et al. were the first in Germany to recognize that a radical surgical technique increased only the complications, not the efficacy of UPPP. The less invasive surgical technique developed based on these findings is still established in Germany. A meta-analysis from 1996 described a success rate of UPPP of about 50%. High-quality randomized trials demonstrate significant superiority of UPPP plus tonsillectomy compared to untreated controls. However, the objective outcome measures of classic UPPP could not be improved even with additional patient selection criteria, and the effects of UPPP often deteriorate over time. To overcome these limitations, various modifications of UPPP have been developed. Due to limited data, evaluation of these new techniques and their comparison with conventional UPPP is difficult at present. In studies comparing a modification of UPPP with the standard approach, the tested modification was demonstrated to be superior. A relevant limitation of the available data results from the small number of institutions (usually not more than two) that investigated the respective modification and the follow-up periods of usually only 6 months. Data are also too sparse to reliably assess complication rates. For conventional UPPP there are considerably more data, wider experience with long-term outcome, and more robust studies examining treatment effects beyond basic respiratory parameters. At present, modifications of UPPP should be principally employed in clinical trials.
Gesehen am 19.09.2018
Online publiziert: 8. Dezember 2016